Review on Davis equation and railway operation power consumption, impact to railway technologies and industrial application - Mahamudin , Nur Shahibrahim (Journal of Emerging Technologies and Industrial Applications, 2024)
Davis Equation is a governing equation that widely use in railway application to describe the total resistance acted on running train. Trainresistance compromise major percentage of overalltrain traction power losses and it gives large impact to train performance and operation power consumption. Davis equation is compromise of three components of train resistances that effect the train motion in many aspect such as train loading, track coefficient of friction and aerodynamics.Several technology had being implemented on nowadays industrial application in term of these three Davis equation components and hadsuccessfully reduced approximate 3% to 25% of operation power consumption.